(untitled) (Research, Society and Development, 2021)
In March 2020, the World Health Organization declared the new coronavirus as pandemic. To contain the infection progressions, the main government through social isolation. At the Federal University of Minas Gerais (UFMG), Emergency Remote Education (ERE) was adopted in order to minimize the impact of the pandemic during the students’ education period. The pandemic’s consequences have also reached and affected the lives of people around the globe in different social, cultural, economic and, particularly, health aspects. With that in mind, was evaluated the general health conditions of UFMG’s Pharmacy’s students, before the ERE. A questionnaire was applied addressing issues related to the socio-demographic profile and students’ habits, general health, physical activity level, medication use and rate of satisfaction with ERE. A total of 401 students answered the questionnaire (39% of the total enrolled students). The CART technique was used in data analysis. Stress, tiredness, exhaustion and anxiety were frequent answers in the questionnaire. However, the attribute with the highest discrimination power was the perception of depression. These results are consistent with the atypical moment around the world. Beyond the uncertainties brought upon us by the pandemic, the ERE brings a new teaching-learning methodology that calls for the students’ protagonism for its full consolidation, accentuating the feeling of stress, exhaustion, anxiety and depression, characterizing the mental illness that students are experiencing. These results highlight the importance of monitoring in adapting to the virtual teaching model, aiming at their better development and the physical and emotional health of the students.